Keanekaragaman Jenis Burung di Kawasan Hutan Mangrove, Resort Pemangkuan Hutan Muara Gembong, Kesatuan Pemangkuan Hutan Bogor - Sasongko, Dwi Agus (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2022)
Muara Gembong Forest Management Unit Resort (RPH), Ujung Krawang Forest Management Unit (BKPH) is an area that has mangroves and is the only one in the Bogor Forest Management Unit (KPH) working area. The mangroves at the Muara Gembong Forest Pemangkuan Resort (RPH) are a habitat for several species of birds. The types of birds that live around mangroves are not always the same as the types of birds that live in the surrounding forest area because of the unique nature of mangrove forests. The research aims to identify the diversity of bird species and their habitat in the Muara Gembong Forest Pemangkuan Resort (RPH). The methods used to determine bird species diversity are point count and IPA. Habitat data collection is done by using vegetation analysis. In the Muara Gembong Pemangkuan Forest Resort (RPH) area, there are 17 species of birds from 12 families with a total of 827 individuals. The diversity of bird species is categorized as being which indicates that the ecosystem is stable in a stable state. In the Muara Gembong Forest Pemangkuan Resort (RPH) area, there are 3 types of vegetation, namely red Pidada (Sonneratia caseolaris), white Api-api (Avicennia marina), and black Api-api (Avicennia alba). The diversity of vegetation types can be referred to as the low category.